Work-Family Conflict and Job Satisfaction: The Mediating Role of Person-Organization Fit Study on Employees of The BRI Aceh Region - Ibrahim, Mahdani; Yusra, Yusra (UI Scholars Hub, 2016)
The objective of this research is to analyze the influence of person–organization fit (P-O fit) on work–family conflict (WFC) and job satisfaction (JS) relationships at Bank Rakyat Indonesia, Aceh Regional in Banda Aceh. The sample includes 127 employees, those who have worked more than two years. The data are collected via questionnaire. The equipment of data analysis is structural equation modeling (SEM), which proceeds using analysis of moment structure (AMOS). The results of the study show the varible P-O fit role as a mediator variable in the relationship of WFC and job satisfaction. WFC does not have a direct effect on job satisfaction